2002
DOI: 10.1176/appi.ap.26.2.76
|View full text |Cite
|
Sign up to set email alerts
|

Management of Terminal Illness: A Medical School-Hospice Partnership Model to Teach Medical Students About End-of-Life Care

Abstract: Physicians are not only called upon to deal with biological, but also with psychosocial issues and concerns in the treatment of the terminally ill. Their training, however, usually does not prepare them to value palliative care, or help them cope with personal feelings about death and possible grief over a patient's loss. The authors describe what one medical school is doing regarding the challenge of preparing medical students to deal more competently and confidently with end-of-life scenarios they will encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Olumsuz tutumların değiştirilebilmesi için, temel hedefi duygusal gelişimi desteklemek olan ölüm eğitimi ve farkındalık programlarına gereksinim vardır. [12,13,21,22]…”
Section: Palyatif Bakımın Niteliğini Artıracak Stratejilerunclassified
“…Olumsuz tutumların değiştirilebilmesi için, temel hedefi duygusal gelişimi desteklemek olan ölüm eğitimi ve farkındalık programlarına gereksinim vardır. [12,13,21,22]…”
Section: Palyatif Bakımın Niteliğini Artıracak Stratejilerunclassified
“…Thematic analysis of remaining articles is summarized in Table 1, including articles discussing hospice placements, 3,54,94 107 technology or online learning, 108,109 simulation, 110 113 and interprofessional learning opportunities. 111 A range of novel teaching methods were also discussed within the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 607 matches for the first two, most involved formal care professionals and facilities concerning the treatment or transfer of dying patients with chronic diseases rather than in-home care of older adults. For example, a sample of the 100 most recent studies showed 21 articles on physician/nurse/medical student training for treating patients at the end of life (e.g., Cowell et al 2002). There were 22 articles dealing with treatment in formal care settings (e.g., Froggatt, Poole, and Hoult 2002;Jacobs, Bonuck, and Burton 2002;Pantilat 2002) and another 14 articles on the experiences or treatment of patients with specific diseases at the end of life (e.g., Bruera 2002;Ganzini, Johnston, and Silveira 2002).…”
mentioning
confidence: 99%